Precise radial velocities of giant stars: IX. HD 59686 Ab a massive circumstellar planet orbiting a giant star in a ~13.6 au eccentric binary system - Ortiz, Mauricio; Reffert, Sabine; Trifonov, Trifon; Quirrenbach, Andreas (Arxiv, 2016)
Context: For over 12 yr, we have carried out a precise radial velocity survey of a sample of 373 G and K giant stars using the Hamilton \'Echelle Spectrograph at Lick Observatory. There are, among others, a number of multiple planetary systems in our sample as well as several planetary candidates in stellar binaries. Aims: We aim at detecting and characterizing substellar+stellar companions to the giant star HD 59686 A (HR 2877, HIP 36616). Methods: We obtained high precision radial velocity (RV) measurements of the star HD 59686 A. By fitting a Keplerian model to the periodic changes in the RVs, we can assess the nature of companions in the system. In order to discriminate between RV variations due to non-radial pulsation or stellar spots we used infrared RVs taken with the CRIRES spectrograph at the Very Large Telescope. Additionally, to further characterize the system, we obtain high-resolution images with LMIRCam at the Large Binocular Telescope. Results: We report the likely discovery of a giant planet with a mass of $m_{p}~\sin i=6.92_{-0.24}^{+0.18}~M_{Jup}$ orbiting at $a_{p}=1.0860_{-0.0007}^{+0.0006}$ au from the giant star HD 59686 A. Besides the planetary signal, we discover an eccentric (